Modelling of diesel engine power generator for grid compliance study - Muhammad Bilal Bin Abu Bakar (2016)
Diesel Generator are being widely used to supplement the power of the grid, or used in conjunction with renewable energy such as Solar Panel and generate active power energy when there is no adequate solar energy. Lastly, Diesel Generator are also used as a backup electrical source due to its fast starting time and fast response.